Small molecule therapeutics to destabilize the ACE2-RBD complex: A molecular dynamics study - Razizadeh, Meghdad (Biophys J, 2021)
The ongoing coronavirus disease 19 (COVID-19) pandemic has infected millions of people, claimed hundreds of thousands of lives, and made a worldwide health emergency. Understanding the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mechanism of infection is crucial in the development of potential therapeutics and vaccines. The infection process is triggered by direct binding of the SARS-CoV-2 receptor-binding domain (RBD) to the host-cell receptor angiotensin-converting enzyme 2 (ACE2). Many efforts have been made to design or repurpose therapeutics to deactivate the RBD or ACE2 and prevent the initial binding. In addition to direct inhibition strategies, small chemical compounds might be able to interfere and destabilize the metastable, prefusion complex of ACE2-RBD. This approach can be employed to prevent the further progress of virus infection at its early stages. In this study, molecular docking was employed to analyze the binding of two chemical compounds, SSAA09E2 and Nilotinib, with the druggable pocket of the ACE2-RBD complex. The structural changes as a result of the interference with the ACE2-RBD complex were analyzed by molecular dynamics simulations. Results show that both Nilotinib and SSAA09E2 can induce significant conformational changes in the ACE2-RBD complex, intervene with the hydrogen bonds, and influence the flexibility of proteins. Moreover, essential dynamics analysis suggests that the presence of small molecules can trigger large-scale conformational changes that may destabilize the ACE2-RBD complex.